2020
DOI: 10.1002/bjs5.50333
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in surgical randomized clinical trials: cross-sectional observational study

Abstract: Background: RCTs provide the scientific basis upon which treatment decisions are made. To facilitate critical review, it is important that methods and results are reported transparently. The aim of this study was to explore transparency in surgical RCTs with respect to trial registration, disclosure of funding sources, declarations of investigator conflicts and data-sharing. Methods: This was a cross-sectional review of published surgical RCTs. Ten high-impact journals were searched systematically for RCTs pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The role of journals in the promotion of transparency by way of strong policies should not be underestimated in improving value and reducing waste in research. 7 , 23 New indicators that valorize research transparency are being developed to incentivize journals to develop and adequately implement these optimal policies. For instance, the “TOP factor” 24 is being developed by the Center of Open Science to assess journals for transparency and openness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of journals in the promotion of transparency by way of strong policies should not be underestimated in improving value and reducing waste in research. 7 , 23 New indicators that valorize research transparency are being developed to incentivize journals to develop and adequately implement these optimal policies. For instance, the “TOP factor” 24 is being developed by the Center of Open Science to assess journals for transparency and openness.…”
Section: Discussionmentioning
confidence: 99%
“…Even data on transparency and on data sharing practices or the promotion of data sharing in the surgical community are scarce. 7 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence indicates that many journals require funding disclosure too [ 31 ]. Whilst there are reports of higher proportions for funding disclosure for randomized controlled trials [ 32 , 33 ], most COVID-19-related research articles have been observational studies, editorials, letters, and reviews, and thus it is logical that most research did not receive funding which would have affected the content of the articles. However, we should bear in mind that even if external funding was not received, it should be stated in order to increase transparency in science.…”
Section: Discussionmentioning
confidence: 99%
“…The picture in dentistry remains considerably bleaker than within biomedical research. A cross‐section of RCTs from the surgical literature, across 10 years and since 2009, has revealed that registration was evident in 84% of the studies overall, whilst prospective registration practices have been identified as increasing increments across the years, from 26% in 2009 to 73% in 2018 (Helliwell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%